Safe disposal of coal bottom ash by solidification and stabilization techniques - Hashemi, Sajedeh Sadat Ghazizadeh; Mahmud, Hilmi; Tan, Chee Ghuan; Ang, Bee Chin; Kuenzel, Carsten; Ranjbar, Navid (Elsevier, 2019)
Solidification and stabilization of coal bottom ash waste (CBA) using CEM1 as the binder have been evaluated in case of leaching as well as the possibility to use this mixture for the construction industry. For this, the CEM1/CBA mass ratio has been varied between 0.5 and 2 and heavy metals leaching of Cu, Cd, Ni and Pb evaluated. Two types of crushed block and whole block leaching tests have been conducted to determine the leaching properties of deionized water, acetic acid and nitric acid leachates. It has been demonstrated that all elements can be immobilized successfully to nearly zero even in the case of a low CEM1 content. Furthermore, it has been shown that more heavy metals leached from the matrix when acetic acid used compared to other leachates. Next to this, the mechanical properties have been tested. After 56 days a compressive strength between 25 and 40 MPa has been measured from 0.5 to 2 CEM1/CBA mass ratios. Based on leaching and compressive strength results, CEM1/CBA mixtures can be considered for the construction industry.